One for all - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Inconvenient Indigenous. Remote Area Development in Botswana, Donor Assistance and the First People of the Kalahari By S Saugestad, Nordiska Afrikainstitutet, Sweden, 2001. 230 pp. ISBN 91 7106 475 3 SEK 220 Euro 23.75